2005
DOI: 10.1017/s0001867800000574
|View full text |Cite
|
Sign up to set email alerts
|

Crack STIT tessellations: characterization of stationary random tessellations stable with respect to iteration

Abstract: Our main result is the proof of the existence of random stationary tessellations in ddimensional Euclidean space with the following stability property: their distribution is invariant with respect to the operation of iteration (or nesting) of tessellations with an appropriate rescaling. This operation means that the cells of a given tessellation are individually and independently subdivided by independent, identically distributed tessellations, resulting in a new tessellation. It is also shown that, for any st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
235
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(237 citation statements)
references
References 10 publications
2
235
0
Order By: Relevance
“…They were formally introduced by Nagel and Weiss (2005). In later papers Nagel and Weiss (2006; have shown that many mean values can be obtained from the characteristic stability property of the tessellations by writing and solving certain balance equations.…”
Section: Fig 1 a Realization Of A Homogeneous And Isotropic Stit Tementioning
confidence: 99%
See 2 more Smart Citations
“…They were formally introduced by Nagel and Weiss (2005). In later papers Nagel and Weiss (2006; have shown that many mean values can be obtained from the characteristic stability property of the tessellations by writing and solving certain balance equations.…”
Section: Fig 1 a Realization Of A Homogeneous And Isotropic Stit Tementioning
confidence: 99%
“…4 shows a realization of a homogeneous but anisotropic STIT tessellation in the 3-dimensional space. In Nagel and Weiss (2005) an explicit construction was presented for such tessellations in a bounded convex window in Euclidean spaces of arbitrary dimension d ≥ 2.…”
Section: Stit Tessellationsmentioning
confidence: 99%
See 1 more Smart Citation
“…[17,23]). Stationary random tessellations that are stable under the operation of iteration -so-called STIT tessellations -were introduced recently by Mecke, Nagel and Weiß [11,12,14] and they may serve as a new mathematical reference model beside the classical Poisson hyperplane or PoissonVoronoi tessellations. On the other hand, the first-order geometry of these tessellations is already determined by two parameters, the surface density and the so-called directional distribution.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent work, [18] proposed to use the Delaunay triangles (rather than the Voronoi polygons) and to aggregate them according to linear networks. Furthermore, line-based tessellations, such as proposed by [37], can also be explored to simulate the geometry of agricultural landscapes.…”
Section: Comparing Tessellation Methods Wrt Original Landscapesmentioning
confidence: 99%